Thermal stability and mechanical properties of hybrid materials based on nitrocellulose grafted by aminopropylisobutyl polyhedral oligomeric silsesquioxane - Yang, X.; Wang, Y.; Li, Y.; Li, Z.; Song, T.; Liu, X.; Hao, J. (Polimery, 2021)
The need for improvement in nitrocellulose (NC) storage safety and convenience of application requires an increase in NC thermal stability and enhancement of its mechanical properties. To this aim, hybrid materials were synthesized by grafting NC with aminopropylisobutyl polyhedral oligomeric silsesquioxane (amino-POSS) using isophorone diisocyanate (IPDI) as a crosslinking agent. The structure and elemental composition of the resulting products were confirmed by Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (1H NMR and 29Si NMR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). It was found, based on the silicon mapping using energy dispersive X-ray spectroscopy (EDS), that amino-POSS was well dispersed in NC matrix. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) studies showed that hybrid amino-POSS-NC materials have higher thermal decomposition activation energy (Ea) compared to NC control sample. According to TGA results, the temperatures of 5 % weight loss (T5 %) and 50 % weight loss (T50 %) as well as the residual masses at 240 °C (CR240 °C), were increased as a result of NC modification with amino-POSS. As can be seen from the digital and scanning electron microscopy (SEM) images, the char layers of amino-POSS-NC hybrid materials after burning in air became more compact with increasing amino-POSS content. XPS studies have shown an increased content of the graphitized carbon in the char residues of the modified samples. The results of DSC, TGA, SEM and XPS studies have directly proved the enhancement of the thermal stability of amino-POSS-NC hybrid materials. In addition, tensile strengths and Young’s moduli of amino-POSS-NC hybrid materials were increased gradually with the amino-POSS content in the uniaxial tensile tests. All these results show that the proposed modification of nitrocellulose improves the safety of manufacture and use of this material.